1970
DOI: 10.3171/jns.1970.33.4.0407
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular size and chronic increased intracranial venous pressure in the dog

Abstract: ✓ Intracranial venous pressure was increased by blocking the torcular Herophili in 10 dogs. At intervals of 1 to 29 weeks, pressure in the superior sagittal sinus and cerebrospinal fluid (CSF) were recorded and the size of the ventricles determined at autopsy. Changes in venous pathways were documented by sinograms. Significant increase in both sagittal sinus and CSF pressures occurred after torcular block. CSF pressures remained elevated for as long as 29 weeks at an average of 100 mm above preblock levels. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

1973
1973
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…even at levels approaching systemic arterial pressure. In an animal model of increased intracranial venous pressure, Guthrie et al [33] reported that although the two pressures were linked, maintenance of a normal pressure gradient persisted. Other authors [34.…”
Section: Discussionmentioning
confidence: 99%
“…even at levels approaching systemic arterial pressure. In an animal model of increased intracranial venous pressure, Guthrie et al [33] reported that although the two pressures were linked, maintenance of a normal pressure gradient persisted. Other authors [34.…”
Section: Discussionmentioning
confidence: 99%
“…All reported cases of elevated venous pressure causing hydrcephalus have been in infants or children who still have a distensible calvarium [6]. Hour and Miller [9] also noted the young age of onset of the dural hypertension of patients who develop hydrocephalus, but they drew no conclusions from this observation.…”
Section: Discussionmentioning
confidence: 84%
“…The relationship between increased intra cranial venous pressure and hydrocephalus has been the subject of several reports [6,10,12]. Unquestionably, massive direct shunting of arterial blood into the venous system or occlusion of important components of the cephalic venous drainage system can cause increased intracranial venous pressure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations